2006
DOI: 10.1097/01.ta.0000199432.88847.0c
|View full text |Cite
|
Sign up to set email alerts
|

Indications for Early Fresh Frozen Plasma, Cryoprecipitate, and Platelet Transfusion in Trauma

Abstract: Early use of plasma and platelets at the upper end of recommended doses appears to reduce the incidence of coagulopathy in massively transfused individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
115
0
8

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(129 citation statements)
references
References 17 publications
4
115
0
8
Order By: Relevance
“…38,39 These guidelines may be appropriate for postoperative bleeding in an otherwise healthy patient but may not be the optimal approach for trauma patients who are hypocoaguable or in shock. 37 A consistent definition of shock according to base deficit values is not well described. We chose to define shock as a base deficit of Ն4 because the normal range of base deficit is Ϫ3 to ϩ3 and recent evidence published in a study of over 800,000 trauma patients that mortality starts to increase at a base deficit above 4.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…38,39 These guidelines may be appropriate for postoperative bleeding in an otherwise healthy patient but may not be the optimal approach for trauma patients who are hypocoaguable or in shock. 37 A consistent definition of shock according to base deficit values is not well described. We chose to define shock as a base deficit of Ն4 because the normal range of base deficit is Ϫ3 to ϩ3 and recent evidence published in a study of over 800,000 trauma patients that mortality starts to increase at a base deficit above 4.…”
Section: Discussionmentioning
confidence: 99%
“…10,37,38,42 Each unit of FFP in addition to coagulation factors contains 0.5 g of fibrinogen. 37 Recent studies suggest that fibrinogen administration is essential for achieving hemostasis in patients with significant traumatic injuries [43][44][45][46][47][48] and very likely contributes to the improved outcomes that have been associated with increased transfusion of plasma. 7,49,50 However, the use of plasma as a volume expander is controversial though this practice has been relatively abandoned since the 1940s.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, routine laboratory tests consider neither the effect of hypothermia on hemostatic physiology nor the complex interaction of plasma proteins, platelets, and the vessel wall after traumatic or surgical injury [8]. Often, the results of routine hemostatic tests are generally available with a delay of at least 30-60 min; results, therefore, may not be able to provide an accurate picture of the current hemostatic physiology [22]. Hardy et al [23] concluded that bedside monitors of hemostasis are needed urgently for the management of operative and trauma-associated bleeding [10][11][12][13][14][15][16][17][18][19].…”
Section: Limitations Of Historical Coagulation Testingmentioning
confidence: 99%
“…Due to the complex nature of hemorrhage in these settings, physicians require coagulation monitoring strategies sensitive to all major possible pathomechanisms of hemostatic dysfunction. POC coagulation monitoring devices have become available and may ultimately overcome several of the limitations associated with routine coagulation testing [3,8,22,25].…”
Section: Limitations Of Historical Coagulation Testingmentioning
confidence: 99%